Jiu jitsu [videorecording (DVD)] - Logothetis, Dimitri; Moussi, Alain, 1981-; Grillo, Frank, 1963-; Yune, Rick, 1971-; Avgeropoulos, Marie, 1986-; Cage, Nicolas, 1965- (Paramount Home Entertainment, 2020)
Every six years, an ancient order of jiu-jitsu fighters joins forces to battle a vicious race of alien invaders. But when a celebrated war hero goes down in defeat, the fate of the planet and mankind hangs in the balance.